Knowledge management as a support for supply chain logistics planning in pandemic cases - Pinto, Carlos Alberto Schettini (Brazilian Journal of Operations & Production Management, 2020)
Objective: This study presents how the knowledge management can be an excellent ally to logistics for planning the supply chain in actions in cases of pandemic. Project / Methodology / Approach: The present study was based on a bibliographic review sought in the main existing databases. From there, it was possible to obtain subsidies to support the proposal of this work. Results: The results showed that a correct application of knowledge management can assist in logistical planning in a very effective way, reducing gaps and shortages, providing very effective actions to mitigate the main obstacles that a pandemic can generate. Research limitations: The most important limitation in this study was the fact that the COVID-19 pandemic is still very active and logistics operations do not yet have effective and consolidated data to bring even more reliable results. Practical implications: According to the conclusions obtained, governmental organizations, at their three levels (municipal, state and federal) should focus on creating public policies that mitigate the problems of supplying of the various matrices of inputs and products. Originality / value: The main contribution of the research lies in the opportunity to present a management component to assist the logistical demands that occur in a pandemic environment.